Legal Minimum Wages and the Wages of Formal and Informal Sector Workers in Costa Rica - T. H. Gindling; Katherine Terrell (Institute for the Study of Labor (IZA), 2004)
The dual economy development models hold minimum wages (among other institutions) accountable for persistent dualism. We use 12 years of micro data on thousands workers in Costa Rica to test whether legal minimum wages have a differential impact on wages in the formal sector vs. informal sector, defined in various ways. We find the evidence from Costa Rica is contrary to the assumptions of these models: increases in minimum wages not only raise wages in the urban formal sector (large urban enterprises) who are covered by minimum wage law, but they also increase the wages of all other workers covered by minimum wage legislation in what are traditionally regarded as informal sectors and where the legislation is often considered not to be enforced (i.e., small urban enterprises, large rural enterprises and small rural enterprises). Further, our results suggest that higher legal minimum wages raise the wage of workers in these ?informal? sectors more than in the urban formal sector and hence may actually work to reduce average wage differentials between these sectors and the urban formal sector. On the other hand, minimum wages have no significant impact on the wages of workers in another sector that is regarded as informal but which is not covered by minimum wage legislation: the self-employed workers (both urban and rural). Thus, minimum wages may contribute to dualism between the formal and informal, defined as self-employed vs. salaried workers. However, we find no evidence that selfemployed earnings are lowered by minimum wages.
Keywords: J31; J23; J38; 330; dual economy; informal sector; minimum wages; wages; Costa Rica; Latin America; Lohnstruktur; Dualökonomie; Informeller Sektor; Schätzung; Costa Rica